Conversion of a continent: contemporary religious change in Latin America - Steigenga, Timothy J.; Cleary, Edward L. (Rutgers University Press, 2007)
A massive religious transformation has unfolded over the past forty years in Latin America and the Caribbean. In a region where the Catholic Church could once claim a near monopoly of adherents, religious pluralism has fundamentally altered the social and religious landscape. Conversion of a Continent brings together twelve original essays that document and explore competing explanations for how and why conversion has occurred. Contributors draw on various insights from social movement theory to religious studies to help outline its impact on national attitudes and activities